2016
DOI: 10.1111/jzo.12398
|View full text |Cite
|
Sign up to set email alerts
|

The role of soil features in shaping the bite force and related skull and mandible morphology in the subterranean rodents of genusCtenomys(Hystricognathi: Ctenomyidae)

Abstract: For rodents that live underground, digging in highly compacted soils requires a higher energy expenditure than digging in poorly compacted soils. We tested how soil hardness affects the bite force as well as the shape and size of the skulls and mandibles of tuco-tucos. Our hypothesis is that species that inhabit harder soils would show a stronger bite force, which should be reflected in the shape of the skull and mandible, while species living in softer soils should have a weaker bite force. We used 24 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…A more confined amount of morphological variation was observed in the mandible of C. minutus ( Fornel et al , 2010 ). This is probably the result of stabilizing selection, since the functions of the mandible are more restricted than in the rest of the skull ( Borges et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A more confined amount of morphological variation was observed in the mandible of C. minutus ( Fornel et al , 2010 ). This is probably the result of stabilizing selection, since the functions of the mandible are more restricted than in the rest of the skull ( Borges et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fornel et al (2010) found significant differences in the skull shape of Ctenomys minutus between habitats (dune and field) in the dorsal, ventral, and lateral views. Based on a comprehensive analysis of 164 individuals from 24 species of the genus Ctenomys , Borges et al (2016) revealed the relationship between skull shape and bite force, as well as the influence of habitat soil compaction on the bite force. A comparison of morphological variations in the skull of animals affected by different environments will help to understand not only the phenotypic variations in the skull but also the life‐history strategies and evolutionary changes in animals (Lu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated interspecific morphological changes in rodents using advanced geometric morphometric techniques (e.g., Alhajeri, 2017; Borges et al, 2016; Maestri et al, 2018; MartĂ­nez & Di Cola, 2011). Geometric morphometrics is a powerful tool for the quantitative analysis of biological and organ morphology (Adams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between skull morphology, bite force, and diet have been investigated in a variety of animal groups, including fish [29,30], lizards [24,31], crocodilians [32], turtles [33], rodents [12,34], birds [23]. Many studies have also focused on bats [19][20][21][35][36][37][38][39][40], but studies involving skull morphology, in vivo bite force, and diets in a single study are limited.…”
Section: Introductionmentioning
confidence: 99%